Effect of corticosteroids combined with cyclophosphamide or mycophenolate mofetil therapy for IgA nephropathy with stage 3 or 4 chronic kidney disease: A retrospective cohort study - Jia, Qing; Ma, Feng; Zhao, Jin; Yang, Xiaoxia; Sun, Ruiling; Li, Rong; Sun, Shiren (Frontiers in Pharmacology, 2022)
Background: To determine the safety and efficacy of corticosteroids (CS) combined with cyclophosphamide (CTX), compared with CS combined with mycophenolate mofetil (MMF) for IgA nephropathy (IgAN) patients with stage 3 and 4 CKD and proteinuria ≥ 1.0 g/24 h in a ten-year real-world study. Methods: We recruited 296 IgAN patients with renal insufficiency and proteinuria ≥ 1.0 g/24 h who received uncontrolled supportive care (USC) (n = 44), CS+CTX therapy (n = 164) and CS+MMF therapy (n = 88) in Xijing Hospital from July 2008 to December 2019. The combined event was defined as a ≥ 50% decrease in eGFR, ESRD, or death. Results: The median of the follow-up period was 39.3 months. One hundred and twenty-five patients experienced the combined event, 65.9%, 37.8%, and 38.6% in the USC, CS+CTX, and CS+MMF group, respectively. In multivariate Cox regression analyses, CS combined with CTX (HR = 0.457, 95% CI 0. 238-0.878, P = 0.019) significantly reduced the incidence of the combined event, whereas CS+MMF (HR = 0.523, 95% CI 0.246-1.109, P = 0.091) did not reduce the risk of the combined event, compared with USC. The incidence of pneumonia and death due to infection in the CS+MMF group was higher than other two groups. Conclusions: Compared with USC and CS+MMF therapy, CS+CTX therapy was more safety and possibly more effective. The results need to be further confirmed by large randomized controlled studies.